Parent-reported quality of life in children with cochlear implants differs across countries - Warner-Czyz, Andrea D.; Nelson, Jackie A.; Kumar, Roshini; Crow, Sarah (Frontiers in Psychology, 2022)
Pediatric cochlear implantation affects communication skills and quality of life, specifically how children interact with others and feel about themselves. Numerous studies worldwide examine well-being among pediatric cochlear implant users, but none to date compare condition-specific quality of life across countries. This retrospective study compares parent-reported cochlear implant-specific quality of life summary data across 14 published studies spanning 11 countries and 9 languages. Sample size ranged from 7 to 370 participants, and children across studies varied in mean chronologic age (3.1–12.2 years), implantation age (1.5–4.6 years), and cochlear implant experience (1.3–8.2 years). Parents completed the Children with Cochlear Implants: Parental Perspectives (CCIPP) questionnaire, an instrument assessing parent-reported cochlear implant-specific quality of life, in their home language. Analysis of variance tests were run for each CCIPP subscale across studies using summary data to determine significant differences between published manuscripts. Across countries, parents of children with cochlear implants appraise communication, social relations, and self-reliance most positively, and the effects of implantation and supporting the child least positively. Cross-country analyses revealed a significant effect of study (country) on quality of life ratings in each domain, with the largest differences in the communication domain. Limited access to implant-related accommodations, cultural awareness of hearing loss, and varying parent expectations may explain country differences in parental ratings of quality of life. Culturally sensitive psychoeducation for the entire family may foster improved life satisfaction for pediatric cochlear implant users and their families.